2021
DOI: 10.1590/1678-4324-2021200663
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and In Vitro Antimicrobial Activity of the Essential Oil Obtained from Eugenia pyriformis Cambess. (Myrtaceae)

Abstract: Our study aimed to evaluate the chemical composition of the essential oil from the leaves of Eugenia pyriformis Cambess., belonging to the Myrtaceae family and native to the Brazilian Atlantic forest. The volatile compounds in the essential oil were extracted by hydrodistillation and analyzed using GC-MS; 36 compounds accounted for 78.80% of the total oil content. The major compounds were β-caryophyllene, bicyclogermacrene, globulol, and δ-cadinene. We evaluated their antimicrobial potential of the essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In comparison with another analysis of the essential oil of leaves of E. pyriformis by Stefanello and coauthors [35]. Other studies with E. 224 pyriformis identified as major compounds β-caryophyllene, bicyclogermacrene, globulol, and δ-cadinene and 225 terpinene-4-ol as minor compound similar to the current study [36]; the compounds 1,8-cineol and terpinen-4-ol were observed in this study. Limonene (14.8%), nerolidol (11.0%), α-cadinol (10.3%), caryophyllene oxide (9.9%) and β-pinene (7.1%) were observe as major compounds by Durazzini and coauthors [37], differing from the compounds found in this study, revealing variation in the constituents.…”
Section: Essential Oil Analysissupporting
confidence: 88%
“…In comparison with another analysis of the essential oil of leaves of E. pyriformis by Stefanello and coauthors [35]. Other studies with E. 224 pyriformis identified as major compounds β-caryophyllene, bicyclogermacrene, globulol, and δ-cadinene and 225 terpinene-4-ol as minor compound similar to the current study [36]; the compounds 1,8-cineol and terpinen-4-ol were observed in this study. Limonene (14.8%), nerolidol (11.0%), α-cadinol (10.3%), caryophyllene oxide (9.9%) and β-pinene (7.1%) were observe as major compounds by Durazzini and coauthors [37], differing from the compounds found in this study, revealing variation in the constituents.…”
Section: Essential Oil Analysissupporting
confidence: 88%
“…Regarding antibacterial activity, the greater antibacterial potential was against Listeria monocytogenes and Salmonella Typhimurium . Souza et al (2021) reported that essential oil from the leaves of E. pyriformis β-Caryophyllene (17.82%), Bicyclogermacrene (12.84%), Globulol (5.96%) and δ-Cadinene (4.33%)) showed MIC values of 250 and 125 μg mL −1 against S. aureus and methicillin-resistant S. aureus (MRSA), respectively. β-caryophyllene, one of the majority in the present study, was reported activity on Gram-negative and Gram-positive bacteria ( Dahham et al, 2015 ), with MIC values for S. aureus (32 μg mL −1 ) ( Santos et al, 2021 ), S. typhimurium (500 μg mL −1 ) and E. coli (10,000 μg mL −1 ) ( Neta et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated Eugenia species' antimicrobial properties against gram‐positive and gram‐negative bacteria and yeast fungi, attributed to compounds like alkaloids, lignins, phenolics, and terpenoids (De Souza et al ., 2018). Uvaia essential oil demonstrated promising activity against methicillin‐resistant S. aureus (MRSA) with a MIC value of 125 μg mL −1 , a significant finding given MRSA's antibiotic resistance (de Souza et al ., 2021). Additionally, uvaia seeds exhibited antimicrobial activity against various strains, including E. faecalis , C. albicans , C. krusei , C. parapsilosis , S. aureus , B. cereus , P. aeruginosa , L. innocua , and E. coli (de Araújo et al ., 2019).…”
Section: Biological Activitiesmentioning
confidence: 99%